Cara Mudah Mempelajari Sejarah Nabi Saw Untuk Tingkat MI/SD - Nur Azizah Zulkifli (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
ABSTRACT This study aims to examine simple and effective learning strategies for studying the history of the Prophet Muhammad (peace be upon him) at the Madrasah Ibtidaiyah (MI)/Elementary School (SD) level. The background of this study is the low interest and understanding of students in the history of the Prophet Muhammad (peace be upon him) due to teaching methods that tend to be textual and focused on memorization. Using a descriptive qualitative approach, data was obtained through observation, interviews, and analysis of learning documents. The results indicate that storytelling strategies, visual-digital media, role-playing methods, and project-based learning are more effective in increasing motivation, understanding, and internalization of the exemplary values ​​of the Prophet Muhammad (peace be upon him) in students. The integration of the values ​​of the Quran, hadith, and the views of Islamic scholars strengthens students' cognitive, affective, and spiritual aspects, making learning more meaningful. This study concludes that a simple yet contextual approach to teaching the history of the Prophet Muhammad (peace be upon him) can be a pedagogical solution in shaping children's Islamic character from an early age, while also providing practical implications for teachers, schools, and curriculum developers.